2012
DOI: 10.2139/ssrn.2048554
|View full text |Cite
|
Sign up to set email alerts
|

Becker Meets Ricardo: Multisector Matching with Social and Cognitive Skills

Abstract: This paper presents a tractable framework for studying frictionless matching in school, work, and marriage when individuals have heterogeneous social and cognitive skills. In the model, there are gains to specialization and team production, but specialization requires communication and coordination between team members, and individuals with more social skills communicate and coordinate at lower resource cost. The theory delivers full task specialization in the labor and education markets, but incomplete specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The developed notion of PAM also helps to shed light on several results in the literature where matching occurs based on multiple variables, suggesting that this framework is useful for deriving closed forms beyond the quadratic-Gaussian case. McCann et al [2012] analyze, amongst other things, a marriage market where agents match based on cognitive and social skills. Under the assumption of identical distributions (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The developed notion of PAM also helps to shed light on several results in the literature where matching occurs based on multiple variables, suggesting that this framework is useful for deriving closed forms beyond the quadratic-Gaussian case. McCann et al [2012] analyze, amongst other things, a marriage market where agents match based on cognitive and social skills. Under the assumption of identical distributions (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is consistent with Bagues and Perez-Villadoniga (2012), who showed that in a natural experiment, recruiters favor candidates who are equivalent to their own assortment of skills to work together as a team. Since the assortative matching occurs only through cognitive ability, in the labor market, a worker lacking social skills but possessing excellent cognitive ability may nonetheless have a high wage (McCann, Shi, Siow, & Wolthoff, 2012).…”
Section: Introductionmentioning
confidence: 99%